2015
DOI: 10.1097/aln.0000000000000862
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of the Open Lung Approach in Patients with Early, Mild, Diffuse Acute Respiratory Distress Syndrome

Abstract: The OLA decreases the driving pressure and improves the oxygenation and lung mechanics in patients with early, mild, diffuse ARDS. EIT is useful to assess the impact of OLA on regional tidal volume distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 42 publications
2
51
0
3
Order By: Relevance
“…Vt and PEEP observed on day 1 were not associated with survival. Conversely, reductions in Vt or increases in PEEP driven by random treatment-group assignment were beneficial only if they were associated with decreases in the driving pressure (data in [92]; Fig. 2 in [17]).…”
Section: Physiology-based Trialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Vt and PEEP observed on day 1 were not associated with survival. Conversely, reductions in Vt or increases in PEEP driven by random treatment-group assignment were beneficial only if they were associated with decreases in the driving pressure (data in [92]; Fig. 2 in [17]).…”
Section: Physiology-based Trialsmentioning
confidence: 99%
“…prevention of cyclical collapse at end-expiration by positive end-expiratory pressure (loop B in rabbits: Fig. 5 in [174]) rather than to recruit alveoli by recruiting maneuvers, at end-inspiration Finally, a comparison showed differences between trial-PEEP (PEEP at which the greatest PaO 2 improvement is observed [80] [These data suggest (Table 1, part II) to: a) ascertain severe ARDS: P/F < 100 after 30 min (Vt ~7 mL kg -1 , PEEP = 10 cm H 2 O, and FiO 2 = 1) [20] or preferably PEEP = 5 cm H 2 O according to the Berlin definition [19] and Grasso [92] b) perform investigations (CT scan, fiberoptic bronchoscopy, etc.) and iterative echocardiography/circulatory optimization upfront c) move early to alveoli recruitment (minimize alveolar "penumbra") using an esophageal catheter or a trial-PEEP (keeping in mind that an SaO 2 = = 88−92% is to be considered in the setting of CMV [141,160], while an SaO 2 = 95−100% is to be considered in the setting of SV [161]]…”
Section: ) Trial Peepmentioning
confidence: 99%
See 3 more Smart Citations